Entrepreneurship Education for the Youth to Support the Entrepreneurial Aspirations of the Younger Generation - Kiki Joesyiana; Nia Anggraini; Arief Rifa’i Harahap; Roza Mildawati (Pasundan Community Service Development, 2023)
The aim of this community service is to provide education and knowledge to the younger generation, enabling them to realize their entrepreneurial aspirations and play a direct role in the local economy. The community service takes place in RT. 03 RW. 02, Bandar Raya Village, Payung Sekaki District, and involves teenagers and students, particularly the local youth, as participants in the counseling sessions. The methodology used in this community service includes lecture-style presentations and question-and-answer sessions. The lecture-style presentations are employed to deliver general knowledge about entrepreneurship education to the younger generation, aiming to foster their interest in entrepreneurship. The question-and-answer sessions are used to address specific topics that may not have been fully covered in the lecture-style presentations. This counseling program involves business practitioners from various business activities in the vicinity of the counseling location. It directly involves faculty members from the Management Study Program at STIE (School of Economics) and lecturers from Universitas Islam Riau, as well as teenagers/students from RT. 03 RW. 02, Bandar Raya Village, Payung Sekaki District, who serve as the target subjects of the program.